Does Asian credit default swap index improve portfolio performance? - Chatchai Khiewngamdee (2018)
© Springer International Publishing AG 2016. This study aims to find whether adding Asian Credit Default Swap (CDS) index will improve the portfolio performance. We introduce a new approach namely Markov switching copula approach to estimate the dependence between asset returns and evaluated the risks of the portfolio by using Value at Risk and Expected Shortfall. The empirical results show that the risk level in high dependence regime is less than in low dependence regime. We also find that including Asian CDS index in portfolio clearly increases the portfolio return.